Internet connectivity disruption in Iraq (Iraq) - Voidly (2026)
CRITICAL severity disruption detected in Iraq. Confidence: 67%. Data sourced from IODA.
Network Disruption Incident ID: IQ-2026-0124
Keywords: internet disruption; IQ; disruption; critical